African economic development evidence, theory, policy - Cramer, Christopher (New York Oxford University Press, 2020)
This book challenges conventional wisdoms about economic performance and possible policies for economic development in African countries. Its starting point is the striking variation in African economic performance. Unevenness and inequalities form a central fact of African economic experiences. The authors highlight not only differences between countries, but also variations within countries, differences often organized around distinctions of gender, class, and ethnic identity. For example, neo-natal mortality and school dropout have been reduced, particularly for some classes of women in some areas of Africa. Horticultural and agribusiness exports have grown far more rapidly in some countries than in others. These variations (and many others) point to opportunities for changing performance, reducing inequalities, learning from other policy experiences, and escaping the ties of structure, and the legacies of a colonial past. The book rejects teleological illusions and Eurocentric prejudice, but it does pay close attention to the results of policy in more industrialized parts of the world. Seeing the contradictions of capitalism for what they are - fundamental and enduring - may help policy officials protect themselves against the misleading idea that development can be expected to be a smooth, linear process, or that it would be were certain impediments suddenly removed. The authors criticize a wide range of orthodox and heterodox economists, especially for their cavalier attitude to evidence. Drawing on their own decades of research and policy experience, they combine careful use of available evidence from a range of African countries with political economy insights (mainly derived from Kalecki, Kaldor and Hischman) to make the policy case for specific types of public sector investment"
Includes bibliographical references (pages [255]-303) and index.
Keywords: Economic development--Africa.